Analysis of engine motor oils by X‐ray absorption and X‐ray fluorescence spectroscopies. (29th May 2014) - Lützenkirchen‐Hecht, D.; Müller, L.; Hoffmann, L.; Wagner, R.
<x xml:space="preserve">Abstract</x> The molecular structure of lubricating motor oils is investigated by X‐ray absorption fine structure spectroscopy measurements. Both fresh and used oils are studied. Although the Zn K‐edge spectra gave information about the degradation of the antiwear/antioxidant zinc dialkyl dithiophosphate (ZDDP) additives within the oil, Fe K‐edge spectra are representatives for iron species dispersed in the oil during operation at elevated temperatures and pressures in the engine. The detailed analysis of the measured data shows that substantial differences are detectable in the spectra of the fresh and used oil. Our results show that the Zn–S bonds of the ZDDP are decomposed during the operation, resulting in Zn–O bonds instead. Furthermore, sixfold Fe–O bonds similar to those in Fe2O3 are found within the used oil, suggesting the presence of debris from the antiwear film of lubricated motor parts in the used oil. Copyright © 2014 John Wiley & Sons, Ltd.